Geomorphology of Las Derrumbadas dome complex, Puebla Mexico - J. A. Muñiz-Jáuregui; C. S. Guzmán-Cervantes; V. H. Garduño-Monroy; A. Jiménez-Haro; P. Layer (Journal of Maps, 2019)
This paper comprises a geomorphologic map of the Las Derrumbadas (LDR) volcanic complex in Mexico. The complex stretches over more than 285 km2, the stratigraphic column encompasses a range age from Cretacious to Quaternary. The methodology used involved the analysis of digital morphometric models, satellite imagery and absolute datings. The result is a 1:40,000 scale map, which is divided into two large geomorphologic groups in terms of the dominant processes: exogenic and endogenic This, in turn, are divided into various subgroups representing the morphological complexity of the study area, principally related to volcanic processes and their coherence with slope processes.